Case-control study on factors associated with crown fractures in the primary dentition - Patrícia CORRÊA-FARIA; Suzane PAIXÃO-GONÇALVES; Saul Martins PAIVA; Maria Letícia RAMOS-JORGE; Isabela Almeida PORDEUS (Sociedade Brasileira de Pesquisa Odontológica, 2015)
The purpose of the present study was to identify the factors associated with dental trauma in preschool children. This case-control study was nested in a population-based cross-sectional study involving a random sample of 301 children one to five years of age in the city of Diamantina, Brazil. The case group was made up of children with at least one fractured deciduous tooth, and the control group was made up of children with no deciduous tooth fracture. The two groups were matched for age in a proportion of one control for every case. The dependent variable was "dental trauma," diagnosed according to the criteria proposed by Andreasen and Andreasen. The independent variables were overjet, measured and considered accentuated when surpassing 3 mm, and lip coverage, classified as adequate or inadequate. Clinical oral examinations were performed by calibrated dentists. The parents provided information on the socioeconomic indicators. Statistical analysis involved the McNemar test and logistic regression. Each group (case and control) was composed of 92 children. In the bivariate analysis, traumatic dental injury (TDI) was associated with overjet > 3 mm (p = 0.001), inadequate lip coverage (p < 0.001), mother's schooling (p = 0.028) and household income (p < 0.001). In the multivariate analysis, only inadequate lip coverage was associated with TDI (OR: 5.35; 95% CI: 1.37-20.85). In conclusion, the case group children had a 5.3 - fold more likely chance of presenting inadequate lip coverage, compared with the control children.